Catalytic asymmetric synthesis of chiral trisubstituted heteroaromatic allenes from 1, 3-enynes. Issue 1 (December 2018) - Yu, Songjie; Sang, Hui; Zhang, Shuo-Qing; Hong, Xin; Ge, Shaozhong
Abstract Chiral allene andN -heteroaryl motifs are present in an ever-growing list of biologically active natural products and synthetic drugs. Although significant progress has been made in asymmetric syntheses of chiral allenes, general and practical protocols for enantioselective syntheses of chiralN -heteroaryl-substituted allenes from readily available starting materials still remain rare. Here we report a highly enantioselective synthesis of quinolinyl-substituted chiral allenes through a copper-catalyzed asymmetric allenylation of quinolineN -oxides with readily available 1, 3-enynes. A variety of 1, 3-enynes react with quinolineN -oxides, affording the corresponding quinolinyl-substituted allenes in high yields (up to 95%) and high enantioselectivities (up to 99% ee). This transformation tolerates a variety of functional groups, such as chloro, bromo, trifluoromethyl ether, tertiary amine, siloxy, carboxylic ester, imide, pyridine, and thiophene moieties. DFT calculations suggest a pathway involving an intramolecular nucleophilic addition of an allenyl copper intermediate with a coordinated quinolineN -oxide through a five-membered, rather than seven-membered, transition state. Chiral allenes are useful chemical reagents, but efficient access to chiral heteroaryl allenes remains challenging. Here the authors report a copper-catalyzed asymmetric allenylation of quinoline N-oxides using 1, 3-enynes, providing efficient access to axially chiral allenes bearing heteroarenes.